2020
DOI: 10.1021/acsami.0c01530
|View full text |Cite
|
Sign up to set email alerts
|

Switching Enhancement via a Back-Channel Phase-Controlling Layer for p-Type Copper Oxide Thin-Film Transistors

Abstract: P-type copper oxide (Cu x O) thin-film transistors (TFTs) with enhanced switching characteristics were fabricated by introducing a sputter-processed capping layer capable of controlling the back-channel phase (labeled as phase-controlling layer, PCL). By optimizing the processing conditions (the deposition power and postdeposition annealing parameters), the switching characteristics of the TFTs achieved a subthreshold swing of 0.11 V dec–1, an on/off current ratio (I on/I off) of 2.81 × 108, and a field-effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…Typically, the previously reported preparation of p-type oxide channels has been presented using conventional vacuum sputtering deposition or sol-gel methods consisting of solution coating and high-temperature sintering. 16,17 However, the outstanding features of the vertical field-effect transistors have thus far been limited to n-oxide channels with spacer layers. 18 Typically, the channel length in vertical transistors has been defined by the thickness of the insulating spacers sandwiched between the source and drain electrodes for electrical isolation, and various spacer materials, such as organic polyimide films and inorganic silicon nitride (Si 3 N 4 ) and silicon oxide (SiO 2 ) layers, have been employed because of their relatively easy and controllable etching process.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the previously reported preparation of p-type oxide channels has been presented using conventional vacuum sputtering deposition or sol-gel methods consisting of solution coating and high-temperature sintering. 16,17 However, the outstanding features of the vertical field-effect transistors have thus far been limited to n-oxide channels with spacer layers. 18 Typically, the channel length in vertical transistors has been defined by the thickness of the insulating spacers sandwiched between the source and drain electrodes for electrical isolation, and various spacer materials, such as organic polyimide films and inorganic silicon nitride (Si 3 N 4 ) and silicon oxide (SiO 2 ) layers, have been employed because of their relatively easy and controllable etching process.…”
Section: Introductionmentioning
confidence: 99%
“…66 Nonetheless, Cu 2 O has seen resonable success, certainly as a proof-of-concept, as a p-type thin-film transistor (TFT). 67 Cr 2 O 3 is an antiferromagnetic insulator with an optical band gap of around 3.4 eV. 68 Strong electron correlation in Cr 2 O 3 results in a conduction band of 3d character, while the valence band is made up of Cr 3d and O 2p orbitals.…”
Section: Oxidesmentioning
confidence: 99%
“…5,124 Cu 2 O can achieve the highest hole mobility, up to 256 cm 2 V À1 s À1 , 65 but when implemented as a TFT the mobility fails to surpass 1 cm 2 V À1 s À1 due to poor interfacing and grain boundaries. 67 SnO also suffers from deposition problems, with SnO 2 formation severely impacting the performance in TFT and complementary metal oxide semiconductor (CMOS) applications. NiO has the better chemical stability of the three, but suffers from low device mobility when implemented as a TFT, likely due to the localised holes generated by acceptor defects.…”
Section: An Outlook On Applicationsmentioning
confidence: 99%
“…The poor electrical performances of Cu2O TFTs was attributed to a high density of defects at grain boundaries and at the semiconductor/dielectric interface, e.g., VOs and CuO secondary phase [21]. Several strategies are proposed to control these defects and to improve the performance and stability of Cu2O TFTs, including surface passivating [22,23], doping [24], using high-κ gate dielectrics (Al2O3, HfO2) [6]. For example, Chang and Nomura et al recently demonstrated the use of sulfur to reduce back-channel defect of p-type CuxO TFTs and achieved μsat of 1.38 cm 2 /Vs and on/off ratio of 4.1 × 10 6 [21].…”
Section: Cu2o Based Devicesmentioning
confidence: 99%